2012
DOI: 10.1016/j.addbeh.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Maternal predictors of comorbid trajectories of cigarette smoking and marijuana use from early adolescence to adulthood

Abstract: This is the first study to examine maternal predictors of comorbid trajectories of cigarette smoking and marijuana use from adolescence to adulthood. Participants (N=806) are part of an on-going longitudinal psychosocial study of mothers and their children. Mothers were administered structured interviews when participants were adolescents, and participants were interviewed at six time waves, from adolescence to adulthood. Mothers and participants independently reported on their relationship when participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…This is consistent with findings from Miller-Day (2008), who found that 'no-tolerance rules' are negatively related to adolescent cannabis use among university students. Apart from these differences between substances, similarities may not be discarded, e.g., settings and motivations for use may be similar and co-occurrence is common (Brook et al, 2012). The abovementioned differences and similarities may explain why tobacco-and alcohol specific rules may be insufficient in explaining adolescent drug use, while cannabis-rules are related to cannabis in a comparable way.…”
Section: Cannabis-specific Parenting Practicesmentioning
confidence: 95%
See 1 more Smart Citation
“…This is consistent with findings from Miller-Day (2008), who found that 'no-tolerance rules' are negatively related to adolescent cannabis use among university students. Apart from these differences between substances, similarities may not be discarded, e.g., settings and motivations for use may be similar and co-occurrence is common (Brook et al, 2012). The abovementioned differences and similarities may explain why tobacco-and alcohol specific rules may be insufficient in explaining adolescent drug use, while cannabis-rules are related to cannabis in a comparable way.…”
Section: Cannabis-specific Parenting Practicesmentioning
confidence: 95%
“…Furthermore, while co-occurrence rates of tobacco and cannabis use are high (Brook et al, 2012) and tolerant tobacco rules and maternal tobacco use are found to be associated with higher levels of adolescent cannabis use (Brook et al, 2012;de Looze et al, 2012a), earlier studies have not taken these factors into account when studying cannabis-specific parenting.…”
Section: Introductionmentioning
confidence: 96%
“…Some report few substance use trajectories, including a large normative group (low use, slight to moderate increases over time) and one or two smaller groups exhibiting more dramatic escalations in use (Flory, Lynam, Milich, Leukefeld, & Clayton, 2004; Li, Duncan, & Hops, 2001; Spaeth, Weichold, Silbereisen, & Weisner, 2010). Others report multiple trajectories, distinguished by varying levels of use at baseline and rates of change over time (Brook, Rubenstone, Zhang, & Brooko, 2012; Martino, Ellickson, & McCaffrey, 2009; Orlando, Tucker, Ellickson, & Klein, 2005; Van Der Vorst, Vermulst, Meeus, Dekovis, & Engels, 2009). Although important, these findings do not necessarily illuminate the substance use patterns that characterize AI adolescents.…”
Section: A Developmental Perspective On the Roots Of Substance Disparmentioning
confidence: 99%
“…Comorbid substance use may stem from both genetic and psychosocial factors (1,9,10). Increasing evidence points to a genetic overlap in the propensity to use tobacco, alcohol, and marijuana (10,11), and factors such as behavioral undercontrol, poor familial relationships, affiliation with deviant peers, and drug accessibility may also predispose the individual to heterogeneous substance use (1,12,13). Therefore, a better understanding of distinct patterns of comorbid substance use may be more practically relevant to prevention and treatment programming than focusing on the use of an individual substance, e.g., marijuana.…”
Section: Introductionmentioning
confidence: 99%